Effect of Availability, Product Quality, Promotion and Price on Consumer Satisfaction of Asus Laptop Users in Banda Aceh City - Yusuf, Zulfan; Rizal, Syamsul (Indonesian Journal Economic Review (IJER), 2022)
This research is motivated by the conditions of competition in the business world in Indonesia from time to time which are getting tighter, so companies must create new marketing strategies to maintain and gain a higher market share. As for the problem of this research is whether the influence of availability, product quality, promotion, and price affect the consumer satisfaction of Asus Laptop users in Banda Aceh City. The purpose of this study was to analyze the influence of each variable, namely availability (XI), product quality (X2), promotion (X3), and price (X4) on consumer satisfaction (Y). The sample in this study were Asus laptop users with 100 respondents as respondents. The sampling technique used a non-probability sampling approach with the convenience sampling method. The method of data collection is done by distributing questionnaires to the respondents. From the results of the research, it is known that the price variable (X4) has the smallest coefficient value, while the promotion coefficient value (X3) has the highest coefficient value, followed by product quality (X2) and availability (X 1). From the results of the research, it is also obtained that simultaneously and partially there is a positive and significant influence between the independent variable and the dependent variable, where tcount > ttable dan Fcount > Ftable.